Pengaruh Metode Pembelajaran Interaktif Berbasis AI dalam Meningkatkan Pemahaman Nilai-Nilai Qurani di Kalangan Siswa Sekolah Dasar - Jumahir; Afga Sidiq Rifai; Sarifa Suhra (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2025)
This research aims to analyze the effect of artificial intelligence (AI)-based interactive learning methods in improving the understanding of Quranic values among students of Pembina Luwuk Elementary School. The scope of the research covers the application of AI technology as an interactive and adaptive learning medium to support the internalization of Quranic values in the context of basic education. This learning method is designed to facilitate students in understanding Quranic concepts through a more engaging and personalized approach. This study used a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of 60 students who were divided into two groups, namely the experimental group using the AI-based learning method and the control group using the conventional method. The research instruments included Quranic values comprehension test, observation, and interview. The results showed that the experimental group experienced a significant increase in understanding of Quranic values with an average posttest score of 85.7, while the control group only reached 72.3. Statistical analysis using an independent t-test showed a significant difference between the two groups (p < 0.05). In addition, observations and interviews revealed that students felt more motivated and actively involved in AI-based learning. The conclusion of this study is that AI-based interactive learning method is effective in improving the understanding of Quranic values among students of Sekolah Dasar Pembina Luwuk. The implication of this study emphasizes the importance of integrating AI technology in the religious learning process to create a more meaningful and relevant learning experience for students